Komparasi Kinerja Reksadana Syariah dengan Reksadana Konvensional - Moch. Amin (Universitas Islam Raden Rahmat, 2019)
The purpose of this study is to determine whether or not there is a difference in mutual fund performance between sharia mutual funds and conventional mutual funds from 2016 to 2018. The data used is secondary data in the form of NVA report data of 34 mutual funds consisting of 16 sharia mutual funds and 18 conventional mutual funds. The data analysis method used is the Jensen Index, Sharpe index, Treynor Index, MM Index, and TT Index methods and uses the t-test to see whether there are differences in mutual fund performance. The results of this study conclude that quantitatively there is no difference in mutual fund performance between sharia mutual funds and conventional mutual funds. Likewise, the statistical test with the t-test shows that there is no difference in performance in terms of the Jensen Index, Sharpe index, Treynor Index, MM Index, and TT Index.